If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6(-6x + -8) = 222 Reorder the terms: 6x + 6(-8 + -6x) = 222 6x + (-8 * 6 + -6x * 6) = 222 6x + (-48 + -36x) = 222 Reorder the terms: -48 + 6x + -36x = 222 Combine like terms: 6x + -36x = -30x -48 + -30x = 222 Solving -48 + -30x = 222 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -30x = 222 + 48 Combine like terms: -48 + 48 = 0 0 + -30x = 222 + 48 -30x = 222 + 48 Combine like terms: 222 + 48 = 270 -30x = 270 Divide each side by '-30'. x = -9 Simplifying x = -9
| -8=x+3+4x | | 8(w-6)+4(-1-5w)=0 | | 58=8x-6 | | 7(y+8)+y=3(y+3)+6 | | 19=-9x-26 | | -7(3x-3)+7=-21x+28 | | 7+1.50x=22.50 | | 3(x-3)-2=6x-3(4+x) | | 40=-16t^2+64x+12 | | 2.5(3.5d+7)=-24.5-5.5d | | 1/2a-1/3=-2 | | -16d+18=-17d | | u/2-u/3=2+2/3 | | 40=-16t^2+64+12 | | 4log[5](3x-5)=2 | | 36x^2+6x-42=0 | | 12x-4y=84 | | -56=6v-8 | | 4x+9+19x+10=180 | | 2y+3=5y+15 | | -2(t-2)+6t=7t-5 | | 4s-2(3s+3)=2s+2 | | 5(3y+20)=-2y+48 | | f(x+9)=x^2-9x-6 | | -25=-5(y+1) | | 23-2x=-5 | | 1/6+1/7= | | u-2/10=3/4 | | y=.378x+150 | | -5/2X=-8 | | 3t+16=t-3 | | 19x+(-1)=-11+14x |